Theory of Deconstruction: A Comparative Study of the Views of Western and Muslim Theorists and Philosophers - Ghulam Sarwar Butt; Ihsan ur Rahman Ghauri (Al-Jami'ah: Journal of Islamic Studies, 2022)
This research paper deals with the theory of deconstruction, as enunciated by French abstruse theorist and philosopher Jacques Derrida. This notable theory is considered to be one of the most significant theories of Postmodernism, a literary and philosophical trend that is famous for its distrust of ideologies and theories whatsoever and stresses the importance of conventions. This literary and philosophical theory challenges our perceived notions regarding text and their meanings by emphasizing the fact that language is nothing but a chain of signifiers. In other words, it means that meanings of a text–worldly or transcendental–are not stable ones; they are unstable and transient. Though this theory has gained much power and prestige in the realm of literature and philosophy; however, this theory has been castigated both by Muslim and Western philosophers and theorists, too. This paper is a humble effort to analyze the views of some well-known and veteran Muslim and Western theorists and philosophers. [Artikel ini bersepakat dengan teori dekonstruksi yang dikenalkan oleh filosof Prancis Jacques Derrida. Sebagai salah satu teori yang penting dalam teori-teori posmodern, kepopulerannya dalam sastra dan filsafat menggoyahkan ideologi dan teori lain serta menekankan pentingnya konvensi umum. Teori sastra dan filsafatnya menantang apa yang sudah kita yakini tentang teks dan makna dengan menekankan fakta bahwa bahasa bukan apa apa selain rangkain pertanda. Dengan kata lain, makna sebuah teks, imanen atau transenden, adalah tidak tetap, mereka labil dan sementara. Walaupun teori ini mendapat posisi kuat dan prestisius dalam sastra dan filsafat, namun disangsikan oleh beberapa pemikir muslim dan barat. Artikel ini merupakan usaha menganalisa pandangan mereka mengenai teori dekonstruksi, baik dari pemikir muslim dan barat.]